2008
DOI: 10.1111/j.1442-9071.2007.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

What do people with glaucoma know about their condition? A comparative cross‐sectional incidence and prevalence survey

Abstract: Patients with established glaucoma have only slightly greater knowledge than newly diagnosed patients, with both patient groups harbouring significant misconceptions regarding glaucoma. Educational programmes and material should be tailored to address these misconceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 22 publications
4
39
1
2
Order By: Relevance
“…16,26 Our intervention involved a number of elements, but these were centred around a prescriptive assessment of health-care needs and beliefs on which education and ongoing support was based. Although education is frequently highlighted as being important in improving adherence, 7,27 we feel as others do, 6,28 that education alone may not adequately tackle the problem.…”
Section: Discussionmentioning
confidence: 99%
“…16,26 Our intervention involved a number of elements, but these were centred around a prescriptive assessment of health-care needs and beliefs on which education and ongoing support was based. Although education is frequently highlighted as being important in improving adherence, 7,27 we feel as others do, 6,28 that education alone may not adequately tackle the problem.…”
Section: Discussionmentioning
confidence: 99%
“…3,[6][7][8] With regards to glaucoma related blindness, lack of awareness and knowledge was found to be an important risk factor. 9,10 The studies from many countries reported that the level of the knowledge and awareness about glaucoma was not only found to be low in general population but also in glaucoma patients. 8,9 For this reason United States of America organizes education programs to increase the knowledge and awareness about glaucoma and the compliance of the patients to the screening programs.…”
Section: Introductionmentioning
confidence: 99%
“…The median educational support score for newly prescribed patients was 12 (range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A sample of the information given is presented in Table 3.…”
Section: Observation Datamentioning
confidence: 99%
“…A lack of glaucoma knowledge is frequently cited as a major cause of poor adherence to ocular hypotensive therapy. [2][3][4][5][6][7] Inconsistencies have been found in the assessment of knowledge; questionnaires range from a small number of general questions to detailed questions about diagnostic procedures, 8 which can cause difficulties in identifying specifics gaps in knowledge that potentially affect adherence.…”
Section: Introductionmentioning
confidence: 99%